2016
DOI: 10.1371/journal.pone.0146299
|View full text |Cite
|
Sign up to set email alerts
|

Size Matters: Individual Variation in Ectotherm Growth and Asymptotic Size

Abstract: Body size, and, by extension, growth has impacts on physiology, survival, attainment of sexual maturity, fecundity, generation time, and population dynamics, especially in ectotherm animals that often exhibit extensive growth following attainment of sexual maturity. Frequently, growth is analyzed at the population level, providing useful population mean growth parameters but ignoring individual variation that is also of ecological and evolutionary significance. Our long-term study of Lake Erie Watersnakes, Ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 44 publications
(62 reference statements)
0
24
0
Order By: Relevance
“…Interpreting this pattern is complicated by extensive individual variation in the asymptotic size of Lake Erie Watersnakes (King et al., 2016) such that larger individuals are not necessarily older. Consequently, it is unclear whether high survival leads to increased body size, large body size leads to increased survival, or some other mechanism underlies variation in both size and survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interpreting this pattern is complicated by extensive individual variation in the asymptotic size of Lake Erie Watersnakes (King et al., 2016) such that larger individuals are not necessarily older. Consequently, it is unclear whether high survival leads to increased body size, large body size leads to increased survival, or some other mechanism underlies variation in both size and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Temporary marks alerted field workers that a snake had been recently processed and that it needs only be scanned before release. Watersnakes were classified as adults if SVL ≥ 430 mm (males) or ≥590 mm (females) (King, 1986; King, Queral‐Regil, & Stanford, 2006; King, Stanford, Jones, & Bekker, 2016). Processing was carried out in the field, at the F. T. Stone Laboratory, our research base during censuses of sites on South Bass, Middle Bass, North Bass and Gibraltar island, or at “South Bay,” a rental property used as our research base during censuses of sites on Kelleys Island.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Lake Erie watersnakes Nerodia sipedon insularum exhibit significant among-individual heterogeneity in asymptotic size. In turn, the fitness benefit of larger size is dependent on annual rates of survival, which may provide a mechanism to maintain growth polymorphisms within the population (King et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Each individual owns a specific genetic factor, resulting in genotypic variation. For example, King et al (2016) found a significant difference in terminal sizes of Lake Erie watersnakes, Nerodia sipedon insularum. Kirkwood and Sommers (1984) proposed an IBM by setting L ∞ to be random.…”
Section: Incorporation Of Individual Variability In Growthmentioning
confidence: 99%